1997
DOI: 10.1074/jbc.272.7.4606
|View full text |Cite
|
Sign up to set email alerts
|

Phosducin, Potential Role in Modulation of Olfactory Signaling

Abstract: Phosducin, which tightly binds ␤␥-subunits of heterotrimeric G-proteins, has been conjectured to play a role in regulating second messenger signaling cascades, but to date its specific function has not been elucidated. Here we demonstrate a potential role for phosducin in regulating olfactory signal transduction. In isolated olfactory cilia certain odorants elicit a rapid and transient cAMP response, terminated by a concerted process which requires the action of two protein kinases, protein kinase A (PKA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…Previous in vitro experiments demonstrated that a 28-mer synthetic peptide representing Trp-643 through Ser-670 of GRK2 prevented association between G␤␥ and GRK2 (9). When permeabilized olfactory cilia were treated with the same peptide, both membrane translocation of GRK3 and desensitization of odorant receptors were inhibited (55). These studies suggest, in agreement with our observations, that in a physiologically relevant setting disruption of G␤␥ binding is sufficient to block efficient GRK3-mediated receptor phosphorylation (55).…”
Section: Figsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous in vitro experiments demonstrated that a 28-mer synthetic peptide representing Trp-643 through Ser-670 of GRK2 prevented association between G␤␥ and GRK2 (9). When permeabilized olfactory cilia were treated with the same peptide, both membrane translocation of GRK3 and desensitization of odorant receptors were inhibited (55). These studies suggest, in agreement with our observations, that in a physiologically relevant setting disruption of G␤␥ binding is sufficient to block efficient GRK3-mediated receptor phosphorylation (55).…”
Section: Figsupporting
confidence: 78%
“…When permeabilized olfactory cilia were treated with the same peptide, both membrane translocation of GRK3 and desensitization of odorant receptors were inhibited (55). These studies suggest, in agreement with our observations, that in a physiologically relevant setting disruption of G␤␥ binding is sufficient to block efficient GRK3-mediated receptor phosphorylation (55). Thus, it is interesting to consider what purpose is served by this combined regulation of GRK2/3.…”
Section: Figsupporting
confidence: 73%
“…sibility of linking G i to the phosphorylation of activated GPR109A via protein kinase A, but our observation that the siRNA knockdown of GRK2 completely inhibited GPR109A internalization indirectly excludes a role for protein kinase A in the regulation of GPR109A internalization. Many studies suggest that GRK2 activity also requires the binding of the G␤␥ subunit (28,59), and the plasma membrane translocation of these kinases is regulated by their association with the G␤␥ subunit (29,60). It is then more likely that PTX pretreatment abolishes GPR109A internalization by inhibiting the association of G␤␥ subunit with GRK2.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, evidence was accumulating for a similar role for Pdc in other G protein signaling systems. It was found that addition of Pdc in vitro or over-expression of Pdc in cultured cells resulted in inhibition of Gβγ-mediated GRK2 [41], GRK3 [42], PLCβ [43] and AC2 [44] activity. These results suggested that Pdc might be a general G-protein regulator through its ability to sequester Gβγ.…”
Section: Early Observations -The Gβγ Sequestration Hypothesismentioning
confidence: 99%